Monetary policy transmission over the leverage cycle: Evidence for the euro area - Leonie Bräuer; Gerhard Rünstler (European Central Bank (ECB), 2020)
We study state dependence in the impact of monetary policy shocks over the leverage cycle for a panel of 10 euro area countries. We use a Bayesian Threshold Panel SVAR with regime classifications based on credit and house prices cycles. We find that monetary policy shocks trigger a smaller response of GDP, but a larger response of in ation during low states of the cycle. The shift in the inflation-output trade-off may result from higher macro-economic uncertainty in low leverage states. For an alternative regime classification based on turning points we find larger effects on GDP during contractions.
Keywords: C32; E32; E44; 330; Monetary Policy; Financial Cycle; Bayesian Threshold Panel VAR